Anticorrosive oligoaniline-containing electroactive siliceous hybrid materials. Issue 69 (29th July 2015) - Gu, Lin; Liu, Shuan; Zhao, Haichao; Yu, Haibin
<x xml:space="preserve">Abstract</x> Advanced anticorrosive coatings were prepared by covalently incorporating electroactive oligoanilines as corrosion inhibitors into inorganic silica.